Water availability development through groundwater investigations and estimates: Case study at Landungsari village, Malang regency - Moh Abduh; Khoirul Abadi; Dandy Achmad Yani (Journal of Community Service and Empowerment, 2024)
The population of Landungsari Village is very large, exceeding 9,000 people. With such a substantial population, the need for clean water and sanitation is also considerable. However, the potential sources of raw water for clean water reserves are very limited, especially surface water. The groundwater level at the study site is also quite deep, particularly in the southern parts of Landungsari Village. Rambakan and Bendungan hamlets have groundwater levels ranging from 15 to 25 meters deep. In contrast, Klandungan hamlet averages over 25 meters, and in the vicinity of Thursina Boarding School, it is more than 40 meters deep, making shallow wells impractical. Meanwhile, the clean water supplied by the PDAM is very limited. To address the issue of clean water availability, an investigation through groundwater estimation is necessary to ensure that the selected locations for deep well exploration are not in vain. The results of groundwater estimation must be representative and provide strong scientific justification for the accuracy of the findings. The method used in this investigation is the geoelectric resistivity method using ADMT-300H, which operates based on Darcy's law. It emits electromagnetic waves and measures soil resistivity to identify aquifer layers and determine the depth and thickness of the aquifer. The results obtained with ADMT-300H include: optimal discharge at well 1 (WL-1) of 3.07 l/s and well 2 (WL-2) of 3.14 l/s. Optimal discharge represents the sustainable limit for utilizing groundwater flow.